2014
DOI: 10.3233/prm-140291
|View full text |Cite
|
Sign up to set email alerts
|

Identifying premature infants at high and low risk for motor delays using motor performance testing and MRS

Abstract: PURPOSE: To determine specific motor skills in premature infants, match those that correlate with standards tests of motor performance, and MRS measures of abnormal brain biochemistry. METHODS: Prospective cohort study of preterm infants (n = 22). Infant motor assessments were completed at term and 12 weeks corrected gestational age (CGA) using the Test of Infant Motor Performance (TIMP) and Bayley Scales of Infant and Toddler Development-III at 12 months CGA. Infants (n = 12) received MRS scans at term CGA. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The timp showed high concurrent validity (r = 0.64) in this comparison (22). Scores on the timp have also demonstrated strong correlations with the findings of fmRi scans of the basal ganglia and white matter of preterm infants at 40 weeks chronological age, and 12 weeks corrected age (23).…”
Section: Instrumentmentioning
confidence: 51%
See 1 more Smart Citation
“…The timp showed high concurrent validity (r = 0.64) in this comparison (22). Scores on the timp have also demonstrated strong correlations with the findings of fmRi scans of the basal ganglia and white matter of preterm infants at 40 weeks chronological age, and 12 weeks corrected age (23).…”
Section: Instrumentmentioning
confidence: 51%
“…The usefulness and sensitivity of the timp in the evaluation of motor performance in both full-term and premature infants has been extensively studied (23,34). It has demonstrated excellent discriminative and predictive capacities for the identification of infants at risk of delayed motor development (9).…”
Section: Resultsmentioning
confidence: 99%
“…Processed spectra were visually inspected for quality of fit, and the metabolite ratio inclusion criterion was the Cramer-Rao lower bound of ,20%. For the TE ¼ 30 ms spectra, the mean (SD) (median, minimum-maximum) of the full width at half maximum was 0.044 (0.033) (0.041, 0.014-0.114) with an SNR of 10 (3) (10,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) for the BG and 0.055 (0.038) (0.043, 0.01-0.114) with an SNR of 10 (3) (9, 6-16) for the WM. For the TE ¼ 270 ms spectra, the full width at half maximum was 0.069 (0.039) (0.060, 0.014-0.143) for the BG with an SNR of 8 (3) (8, 4-14) and 0.045 (0.032) (0.038, 0.010-0.124) for the WM with an SNR of 5 (2) (4, 2-9).…”
Section: Image Acquisition and Processingmentioning
confidence: 99%
“…We developed the Specific Test of Early Infant Motor Performance (STEP) to address this need and have shown that STEP scores at term and 3 months can predict scores on the Bayley Scales of Infant and Toddler Development, Third Edition (Bayley-III) at 12 months. [4][5][6] A recent consensus statement emphasized combining neuroimaging with clinical assessment for improved diagnosis of cerebral palsy. 7 In this study, we determined whether neuroimaging (MR spectroscopy or diffusion MR imaging) reflects STEP performance at term and improves the ability of STEP to predict later development.…”
mentioning
confidence: 99%
“…The Specific Test of Early Infant Motor Performance (STEP) is a novel developmental screening test for preterm infants designed for rapid and early detection of motor problems. In constructing this test, we previously performed Rasch partial credit analysis of all 42 items in the TIMP combined with kinematic study of early infant motor patterns, to select 10 movements that showed the greatest discrimination between preterm infants of different motor abilities [6]. These movements reflect anti-gravity flexion and extension of the head and neck, movement in the arms and legs, and tone in the shoulder girdle and pelvis, which are foundational for high level motor movements in the first year of life.…”
Section: Introductionmentioning
confidence: 99%